Genome-wide association studies for identification of genes and QTLs controlling the palmitic acid content in rice bran oil - Phuong Nga, Mai Thi; Thuy Linh, Nguyen Thi; Mai Huong, To Thi (Vietnam Journal of Biotechnology, 2023)
Rice bran oil is becoming more and more popular plant oil source for human consumption. As one of the biggest producers of rice worldwide, the regulation of rice bran oil contained in Vietnam is becoming more necessary. In the present study, 161 rice accessions, which derive from diverse ecosystems in Vietnam, were used to investigate their palmitic acid (PA) content, the significant Single Nucleotide Polymorphisms (SNPs) as well as candidate genes relating to PA content using genome-wide association studies (GWAS). From the GWAS analysis, sixty-two noteworthy markers and nine quantitative trait loci were detected on chromosomes 1 and 11. Moreover, 187 candidate genes were identified. Notably, we identified the candidate genes including OsFAD and GDSL-like lipase/acylhydrolase, whose function relates to fatty acid (FA) content. Furthermore, the LOC_Os11g27370.1 gene, which encodes UDP-glucuronosyltransferase domain-containing protein, located on qC16.0.11.6, chromosome 11, has been involved in the FA biosynthesis pathway in animals but has not been proven yet in plants. Therefore, this gene could serve as a potential candidate gene to validate its function in rice plants. Other candidate genes with diverse functions were identified from our study but the relation to FA biosynthesis pathway has not been proven yet in any other studies. Therefore, these candidate genes can also open a number of in-depth studies to validate their involvement in FA biosynthesis pathways. The results from this study not only give a deeper knowledge of PA in rice bran oil but also pave the way for future applications in breeding programs aimed at improving the oil profile in rice.